An Investigation of Needs Analysis and the English Textbook Used for Accounting Major Students - Alhaq, Indah Fatihaturrahmah; Wirza, Yanty (International Journal of Education, 2021)
Indonesian government categorized vocational school study program into nine: technology and engineering, information and communication technology, health, agribusiness and agro technology, fisheries and marine, business and management, tourism, fine arts and crafts, and performing arts, each of which requires different teaching materials relevant to the learning outcomes and market demands. Logically, the students from various vocational study programs could not possibly have the same textbook since their needs in the work industry also differ from one another. This study aims to investigate whether the English textbook that 11th-grade students of accounting majors use is compatible with their needs. This study adopted a qualitative study approach, particularly a case study method utilizing needs analysis and document analysis as research instruments. This study found that accounting students need the speaking skill and also vocabulary skills the most for their future careers. It was found that the English textbook used by 11th-grade students of accounting majors could not meet the students’ needs because the materials in the textbook are considered too general. In other words, the textbook is not major-specific to cater for their work contexts. This result suggests that vocational schools are required to conduct a needs analysis before creating teaching materials, especially textbooks for vocational school students.